Older and younger adults differently judge the similarity between negative affect terms. (4th March 2019) - Ready, Rebecca E.; Santorelli, Gennarina D.; Mather, Molly A.
ABSTRACT: Objectives: Theoretical models of aging suggest changes across the adult lifespan in the capacity to differentiate emotions. Greater emotion differentiation is associated with advantages in terms of emotion regulation and emotion resiliency. This study utilized a novel method that directly measures judgments of affect differentiation and does not confound affective experience with knowledge about affect terms. Theoretical predictions that older adults would distinguish more between affect terms than younger persons were tested. Method: Older ( n = 27; aged 60–92) and younger ( n = 56; aged 18–32) adults rated the difference versus similarity of 16 affect terms from the Kessler and Staudinger (2009 ) scales; each of the 16 items was paired with every other item for a total of 120 ratings. Participants provided self-reports of trait emotions, alexithymia, and depressive symptoms. Results: Older adults significantly differentiated more between low arousal and high arousal negative affect (NA) items than younger persons. Depressive symptoms were associated with similarity ratings across and within valence and arousal. Conclusion: Findings offer partial support for theoretical predictions that older adults differentiate more between affect terms than younger persons. To the extent that differentiating between negative affects can aid in emotion regulation, older adults may have an advantage over younger persons. Future research should investigate mechanisms that underlie age group differences in emotion differentiation.